Facile Synthesis of Co-Cu Metal Organic Framework as Efficient Non-Noble Bifunctional Electrocatalysts for Overall Water Splitting - Herrera-Diaz, F; Herrera-Diaz, F (Elsevier B.V., 2024)
The rapid development of superior, highly stable, alkaline-medium-compatible, and nonprecious earth-abundant bifunctional electrocatalysts has garnered significant research interest. This interest aims to replace the costliest noble metals (Pt, Ir/IrO2, and Ru/RuO2) in renewable and green energy technologies for overall water splitting. However, there are still important limitations, such as lower stability and higher energy consumption. In this work, we report the synthesis of Cu-Co metal-organic frameworks (MOFs) as a bifunctional electrocatalyst using a simple chemical precipitation technique. Especially, when 11.5 mM of Co is combined with Cu MOF, it exhibits excellent bifunctional activity for overall water splitting with a lower overpotential of 0.21 V (OER) and -0.71 V (HER) at a current density of 10 mA cm−2, which exhibits nearly several times more enhancement than that of pristine Cu and Co MOFs in a 1 M KOH electrolyte solution. The Tafel slope value of 130 mV/dec and the lower charge transfer resistance, along with relatively high stability for up to 12 h at the onset potential of OER and HER, are observed for the 11.5 mM Cu-Co MOF electrocatalyst. The present results open an alternative pathway for developing a novel design of highly efficient and scalable bifunctional electrocatalysts for overall water splitting. © 2024
Keywords: Cu MOF; Co MOF; Cu-Co MOF; Chemical precipitation technique; Bifunctional electrocatalysts; OER; HER; Water splitting